The Influence of Organizational Culture and Communication on Employee Performance: The Role of Interactional Justice as A Mediation Variable - Pertiwiningsih, Ana; Rozikan, Rozikan (El-Barka, 2024)
Human Resources (HR) is an important aspect of realizing organizational goals. Human resources who are qualified and competent in carrying out their work will make the resulting productivity achieve high performance. One way to increase company productivity is to pay attention to organizational cultures, communication, and interactional justice on employee performance. This research aims to examine the influence of organizational culture and communication patterns on employee performance with interactional justice as a mediating variable. The study in this research is BMT BIF DIY. This research is quantitative research. The sample used in the research was all BMT BIF DIY employees, totaling 78 respondents obtained using the non-probability sampling method. Data were collected using a questionnaire and analyzed using SmartPLS software version 3.2.9. The results of this research show that there is a positive influence between organizational culture on interactional justice, communication patterns have no effect on interactional justice, interactional justice has a positive effect on employee performance, interactional justice can mediate the influence of organizational culture on employee performance, and interactional justice is unable to mediate communication patterns on employee performance. Based on the results of this research, the management of BMT BIF DIY must be able to develop an attitude of mutual respect between each other so that they will feel comfortable at work, thereby increasing a good culture of justice